Supporting Feeding of Late Preterm Infants in the Hospital: A Quality Improvement Project. Issue 6 (November 2021) - Lober, Angela; Tussey, Christina; Gorny, Jenny
Abstract: Background: Feeding difficulty is the most common cause of delayed hospital discharge and readmission of late preterm infants. Frequent and adequate feedings from birth are protective against dehydration, hypoglycemia, and jaundice. The National Perinatal Association's feeding guidelines provide the foundation for late preterm infant standards of care. Feeding at least every 3 hours promotes nutritional status and neurologic development. One feeding assessment every 12 hours during the hospital stay can ensure quality of infant feeding. Problem: At a large urban hospital, medical record reviews were completed to evaluate nursing care practices consistent with the hospital's late preterm infant care standard policy. Feeding frequency and nurse assessment of feeding effectiveness were far below acceptable targets. A quality improvement team was formed to address inconsistency with expected practice. Methods: The project included an investigation using the define, design, implement, and sustain method of quality improvement. Parent education, nurse education, and visual cues were developed to sustain enhanced nursing practice. Results: Late preterm infants who received feedings at least every 3 hours increased from 2.5% (1 of 40) to 27% (11 of 40); ( M = 0.275, SD = 0.446), p = 0.001. Documented breastfeeding assessments increased from 2% (5 of 264) to 8% (10 of 126), p = 0.001. Documented bottle-feeding assessments increased from 15% (39 of 264) to 31% (53 of 172), p < 0.001. Intervention time was cut short due to reprioritization of efforts in response to the COVID-19 pandemic. Conclusion: Interventions and implementation of this process improvement is easy to replicate through attainable and sustainable goals directed toward improved outcomes for late preterm infants. Abstract : Approximately 7.5% of babies born in the United States are classified as late preterm. Late preterm infants often experience feeding challenges that can lead to dehydration, hypoglycemia, and jaundice. Feeding difficulty is the most common cause of delayed hospital discharge and readmission of late preterm infants. In this quality improvement project, nurse and parent education along with a focus on frequent feeding and documentation of feedings led to improvements in overall care of late preterm infants.